Forgiveness and reconciliation - London, H. B.; Kendall, R. T.; Maher, Yvette; Sande, Ken.; Bakker, Jim, 1940- (Colorado Springs, CO : Focus on the Family, 2004)
Host H.B. London and his guests discuss the issues surrounding forgiveness and reconciliation.
H.B. London, Jr., host ; with guests R.T. Kendall, Yvette Maher, Ken Sande, and Jim Bakker.
Compact discs.
In container (21 cm.).
Compact discs.
Keywords: Forgiveness -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity; Forgiveness -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity